NF-κB-responsive miR-155 induces functional impairment of vascular smooth muscle cells by downregulating soluble guanylyl cyclase - Park, Minsik; Choi, Seunghwan; Kim, Suji; Kim, Joohwan; Lee, Dong-Keon; Park, Wonjin; Kim, Taesam; Jung, Jiwon; Hwang, Jong Yun; Won, Moo-Ho; Ryoo, Sungwoo; Kang, Seung Goo; et al. (Experimental & molecular medicine, 2019)
Vascular smooth muscle cells (VSMCs) play an important role in maintaining vascular function. Inflammation-mediated VSMC dysfunction leads to atherosclerotic intimal hyperplasia and preeclamptic hypertension; however, the underlying mechanisms are not clearly understood. We analyzed the expression levels of microRNA-155 (miR-155) in cultured VSMCs, mouse vessels, and clinical specimens and then assessed its role in VSMC function. Treatment with tumor necrosis factor-α (TNF-α) elevated miR-155 biogenesis in cultured VSMCs and vessel segments, which was prevented by NF-κB inhibition. MiR-155 expression was also increased in high-fat diet-fed ApoE −/− mice and in patients with atherosclerosis and preeclampsia. The miR-155 levels were inversely correlated with soluble guanylyl cyclase β1 (sGCβ1) expression and nitric oxide (NO)-dependent cGMP production through targeting the sGCβ1 transcript. TNF-α-induced miR-155 caused VSMC phenotypic switching, which was confirmed by the downregulation of VSMC-specific marker genes, suppression of cell proliferation and migration, alterations in cell morphology, and NO-induced vasorelaxation. These events were mitigated by miR-155 inhibition. Moreover, TNF-α did not cause VSMC phenotypic modulation and limit NO-induced vasodilation in aortic vessels of miR-155 −/− mice. These findings suggest that NF-κB-induced miR-155 impairs the VSMC contractile phenotype and NO-mediated vasorelaxation by downregulating sGCβ1 expression. These data suggest that NF-κB-responsive miR-155 is a novel negative regulator of VSMC functions by impairing the sGC/cGMP pathway, which is essential for maintaining the VSMC contractile phenotype and vasorelaxation, offering a new therapeutic target for the treatment of atherosclerosis and preeclampsia. Vascular disease: Small RNA as a possible culprit The overexpression of a microRNA molecule adversely affects the functioning of vascular smooth muscle cells (VSMCs) and may contribute to the development of artherosclerosis and preeclampsia. The interactions between VSMCs and the cells lining blood vessels (endothelium) are crucial for maintaining the healthy phenotype and relaxation of blood vessels. Disruption to these interactions via inflammation, for example, can trigger serious vascular diseases. Young-Myeong Kim at Kangwon National University, Chungcheon, South Korea, and co-workers demonstrated that expression levels of a microRNA-155 are elevated in patients with artherosclerosis and preeclampsia, while an enzyme found in VSMCs called soluble guanylyl cyclase is considerably reduced. Using human and mice tissues, the team showed that miR-155 impairs the contractile phenotype and relaxation of VSMCs by reducing guanylyl cyclase expression. Their findings may inform new therapies for vascular diseases.